Shielding effectiveness of mesh wire for 50Hz magnetic field - El-Shami, Ibtihal Fawzi (2011)
A wire mesh shield composed of thin conductive wires will influence the behaviour of electromagnetic fields within it. Many researchers have investigated electromagnetic field behaviour in solid metal, but little of this work has probed into the effects of a wire mesh. The primary goal of this work is to design wire mesh shielding under overhead power lines to investigate the electromagnetic energy transmitted to the ground and possibly can exposed people under certain risk.